2022
DOI: 10.1371/journal.pone.0265431
|View full text |Cite
|
Sign up to set email alerts
|

Antibody seroprevalence against SARS-CoV-2 within the Canton of Sarajevo, Bosnia and Herzegovina—One year later

Abstract: Background Serostudies are important resources when following pandemics and predicting their further spread, as well as determining the length of protection against reinfection and vaccine development. The aim of this study was to update data on the prevalence of seropositive individuals in Canton Sarajevo, Bosnia and Herzegovina (B&H) from September 2020 to May 2021. Methods Anti-SARS-CoV-2 antibodies were quantified using an electrochemiluminescence immunoassay. Results Compared to the period April–J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…Patients aged 60–70 years were less at risk of IgM seropositivity, which is consistent with earlier studies [ 17 , 25 , 30 , 39 , 43 , 44 ]. In Bosnia and Herzegovina, Prguda-Mujic and colleagues reported a reduced risk of positive anti-SARS CoV-2 Ig levels in patients aged over 50 years old [ 30 ]. Other studies reported a reduced risk of SARS-CoV-2 positivity in younger individuals [ 16 , 45 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Patients aged 60–70 years were less at risk of IgM seropositivity, which is consistent with earlier studies [ 17 , 25 , 30 , 39 , 43 , 44 ]. In Bosnia and Herzegovina, Prguda-Mujic and colleagues reported a reduced risk of positive anti-SARS CoV-2 Ig levels in patients aged over 50 years old [ 30 ]. Other studies reported a reduced risk of SARS-CoV-2 positivity in younger individuals [ 16 , 45 ].…”
Section: Discussionsupporting
confidence: 92%
“…The overall crude seroprevalence of SARS–CoV–2 was 96.9%, which is consistent with those reported in other settings such as Chile (97.3%) [ 13 ]. In contrast, lower seroprevalence values were recently reported in Portugal (2.7–3.9%), Mozambique (3%), Bosnia and Herzegovina (3.77%), Japan (3.9%), Denmark (5.3%), Chile (7.2%), Spain (9.6–21.9%), Italia (11%), Sweden (11.8%), Iran (14%), Pakistan (16%), Iran (17.1%), Iraq (23.72%), Poland (42.7%), USA (5.6–57.7%), and Lebanon (58.9%) [ 4 , 14 30 ]. Differences in study period, SARS–CoV–2 variants, age groups, prevalence of risk factors and/or comorbidities (e.g., obesity, diabetes, hypertension), and COVID–19 vaccine coverage could explain discrepancies between seroprevalence estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Such knowledge at the level of institutions, regions or entire countries can be very useful for the management of anti-pandemic measures. Therefore, it is not surprising that the results of such seroepidemiological studies are presented in dozens of scientific publications (Anda et al, 2022;Fernández-Rojas et al, 2022;Goldfarb et a.l, 2022;Lewin et al, 2022;Mahallawi et al, 2022;Mercado-Reyes et a.l, 2022;Olariu et al, 2022;Prakash et al, 2022;Prguda-Mujic et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Similar trends were observed in studies of adults ( 22 ). The seroprevalence in Bosnia and Herzegovina among adults for the period from April to July 2020 was 3.77%, and one year later for the same population it was 29.9% ( 23 ). In Bosnia and Herzegovina, the first confirmed cases of COVID-19 were found at the beginning of March 2020, in Sarajevo Canton on 20 th March.…”
Section: Discussionmentioning
confidence: 97%